Species diversity and phenetic relationship among accessions of api-api (Avicennia spp.) in Java based on morphological characters and ISSR markers - fennalia putri sabdanawaty; Purnomo PURNOMO; Budi Setyadi Daryono (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Sabdanawaty FP, Purnomo, Daryono BS. 2021. Species diversity and phenetic relationship among accessions of api-api (Avicennia spp.) in Java based on morphological characters and ISSR markers. Biodiversitas 22: 193-198. Api-api (Avicennia spp.) from mangrove groups is rich in economic and ecological benefits. Research on the potential of api-api has been extensively done, but no research is specifically focused on the identification of api-api. This study aims to identify species diversity and phenetic relationships of api-api in Java based on morphological and molecular characters. The morphological analysis was based on 35 characters and referred to the descriptor. The PCA analysis on the morphological characters of Avicennia spp. showed a high diversity. Morphological characters have a high effect on grouping patterns such as habitat, leaf shape, leaf tip, leaf base, and petal color. Molecular observations were done on the polymorphism of DNA bands. The ISSR primers used were ISSR02, ISSR04, and ISSR10. PCR amplification of DNA was separated and visualized using a doc gel electrophoresis. The results showed a high diversity based on the percentage of DNA polymorphism. The research resulted in three species of Avicennia spp. in Java, namely Avicennia officinalis, A. alba, and A. marina. Phenetic relationships between Avicennia spp. form was based on similarity in character, not based on the area of origin. The environmental conditions in this study slightly opposed the character of Avicennia spp., which presumably due to the similarity in various marine areas of Java such as temperature, pH, and the required salinity.